UNIT TERINTEGRASI ELEKTROKOAGULASI DAN ULTRAFILTRASI UNTUK PENGOLAHAN LIMBAH CAIR TEMPE DI KELURAHAN CIMAHI, KECAMATAN CIMAHI TENGAH - Aryanti, Putu Teta Prihartini; Nugroho, Febrianto Adi; Susilowati, Susilowati (JURNAL WIDYA LAKSANA, 2020)
Cimahi Subdistrict in Cimahi City, Indonesia has two problems related to clean water and tempeh industry wastewater. The communities Cimahi Subdistric used groundwater that contains high concentration of organic compounds as well as dissolved minerals. Meanwhile, the liquid waste from tempe industry was not treated properly, and consequently, it polluted the river when disposed directly. This activity provided technology to solve the mentioned problems in Cimahi Subdistrict, namely ultrafiltration (UF) and integrated electrocoagulation - ultrafiltration (EC-UF) units. In groundwater treatment using UF membrane, the water product meet drinking water quality standards. The integrated EC-UF reduced the turbidity levels of tempeh industry wastewater to below 5 NTU and BOD by 60%. The EC units can be integrated with biological process as the second treatment to produce more clean effluent. This technology can be used as an alternative of green technology for water and industrial wastewater treatment